You are on page 1of 16

# CO-ORDINATE GEOMETRY

INTRODUCTION TO CONCEPT OF CIRCLES

CONTENTS:
1. DEFINITION AND STANDARD FORM
2. NOTATIONS AND APPLYING CONDITIONS ON POINT
AND LINE
3. EQUATION OF TANGENT, NORMAL TO CIRCLE
4. PARAMETRIC EQUATIONS OF CIRCLE
5. PROPERTIES OF CIRCLE
6. HOMOGENIZING CIRCLE
------------------------------------------------------------------------------------
INTRODUCTION
The method of describing the location of points in this way was proposed by the
French mathematician René Descartes (1596 - 1650). (Pronounced "day
CART"). He proposed further that curves and lines could be described by
equations using this technique, thus being the first to link algebra and geometry.
In honor of his work, the coordinates of a point are often referred to as its
Cartesian coordinates, and the coordinate plane as the Cartesian Coordinate
Plane.

Recall that a plane is a flat surface that goes on forever in both directions. If we
were to place a point on the plane, coordinate geometry gives us a way to
describe exactly where it is by using two numbers.
1.DEFINATION AND STANDARD FORM OF CIRCLE

Circle is the locus of points equidistant from a given point, the center of the
circle. The common distance from the center of the circle to its points is called
radius. Thus a circle is completely defined by its center (O) and radius (R):

C (O, R) = O(R) = {x: dist (O, x) = R}.
Let (x1 , y1) is the center and r is the radius of the circle then the equation of the
circle is given by
C(O, R) = O(R) = {x: dist(O, x) = R}.
i.e, (x-x1)2+(y-y1)2 = r2
expanding the equation we get the result that equation of every circle is
1) second degree equation in x,y .
2)coefficient of x2 =coefficient of y2.
3)coefficient of xy =0.
So,standard form of the circle is given by x2+y2+2gx+2fy+c = 0.
This can be rearranged as (x+g)2 + (y+f)2 = (g2+f2-c) reprensents a circle
with (-g,-f) as center and (g2+f2-c)1/2 as radius.
From general equation i.e, (x-x1)2+(y-y1)2 = r2
r2 is always positive or zero so,
1) g2+f2-c >0  real circle.
2) g2+f2-c =0  point circle (circle represented by its center)
3) g2+f2-c <0  imaginary circle .

Examples :

1) Convert this equation into center-radius form. State the coordinates of the
center of the circle and its radius.

Center = (-1,2)

2) Write the general form equation for the circle whose graph is shown at the
right. List 5 points that lie on this circle.
Center = (1, 2) Radius = 4

Points on the circle:
(1, 6), (1, -2), (5, 2), (-3, 2) read off
the graph. Choose any x-value in
circle.
Let x = 2 and find y.

Last two points on circle:

2. NOTATIONS AND APPLYING CONDITIONS ON POINT
AND LINE
Notations:
Let S = x2+y2+2gx+2fy+c then
S1= xx1+yy1+g(x+x1)+f(y+y1)+c
S12 = x1x2+y1y2+g(x 1+x2)+f(y 1+y2)+c
S11 = x12+y12+2gx1+2fy1+c

Applying conditions on points and lines:
IF S = 0 is a circle p(x1,y1) is a point then square of the Distance from center to
point is (g+x1)2+(f+y1)2
Taking the condition
(g+x1)2+(f+y1)2-g2-f2+c =S11
1) S11 > 0  p lies out side the circle.
2) S11 =0  p lies on the circle.
3) S11 < 0  p lies inside the circle.
IF ‘C’ is center ‘r’ is the radius of a circle and the perpendicular distance from
center C to line ‘L = 0’ is ‘d’ then
1) d > r  L = 0’ is outside the circle.
2) d= r  L = 0’ touches the circle.
3) d < r  L = 0’ cuts the circle in two distant points.

3. EQUATION OF TANGENT, NORMAL TO CIRCLE

For a circle (x-x1)2-(y-y1)2 =r2 tangent with a slope m is given by distance from
center to line y=mx+c is equal to radius 
y1-mx1-c = ±(1+m2)1/2r 
c = y1-mx1 ± (1+m2)1/2r
Substituting value of c in the general equation of circle
y = mx +c we get y = mx+y1-mx1±(1+m2)1/2r
equation of tangent to circle is given by
(y-y1) = m(x-x1) ±r(1+m2)1/2.
Considering circle S equation of tangent at (x1,y1) on the circle is derived
By substituting (x1,y1) in circle equation
Equation of tangent to circle S=0 is given by S1=0
Form definition , normal is any line perpendicular to tangent at the point of
contact.It
It passes through the center of the circle
Normal
ormal to a circle with tangent slope m, center (x1,y1) is given by
(y-y1)+m(x-x1) =0
Equation of normal of the circle S=0 at p(x1,y1) is given by
(y+f)(x1+g)=(x+g)(y1+f).

Examles:

1) Write the general equation of a circle that is tangent to the X-axis
X with a
center located at (4, -6)?
Solution:
Center (4, -6) and radius 6.

2) Find the equations of tangent and normal to the circle x² +y² -5 x +2 y
+3 = 0 at the point (2, -3).

Solution:

The given circle is x² +y² -5 x +2 +2 y +3 = 0 ... (i)
The equation of the tangent to the circle (i) at the point P (2, - 3) is
x. 2 + y. (-3) -5.(1/2).(x +2) +2.(1/2).(y/3) +3 = 0
=> 4 x -6 y -5 x -10 +2 y -6 +6 = 0
=> -x -4 y -10 = 0 => x +4 y +10 = 0
The slope of the tangent at P = - 1/4
=> the slope of the normal at P = 4
The equation of the normal to the circle (i) at P (2, -3) is
y +3 = 4 (x - 2) i.e. 4x - y -11 = 0

Exercise:

1. Find the equations of the tangent and the normal to the circle x² +y² = a2
at (x1,y1)

2. Find the equations of the tangent and the normal to the following circles
at the given points.
(i) x² +y² = 169 at (12, - 5)
(ii) 4 x² +4 y² = 25 at (3/2, -2)
(iii) x² + y² -4 x +2 y +3 = 0 at (1, -2)
(iv) 3 x² +3 y² -4 x -9 y = 0 at the origin.
3. Find the equations of the tangent and the normal to the following circles:
(i) x² +y² = 10 at the points whose abscissa is 1.
(ii) x² +y² -8 x -22 y +12 = 0 at the points whose ordinate is -1.
4. Show that the tangents drawn at the points (12, - 5) and (5, 12) to the
circle x² + y² = 169 are perpendicular to each other.

1. x x1 +y y1 = a² ; y1 x -x1 y = 0
2. (i)12 x -5 y -169
169 = 0; 5x +12 y = 0
(ii) 6x +8 y +25 = 0; 4x -3y = 0
(iii) x +y +1 = 0; x -y -33 = 0
(iv) 4 x + 9 y = 0; 9 x -44 y = 0
3. (i) x +3 y -10 = 0, x -33 y -10 = 0, 3 x -y = 0,
(ii) x -2 y -77 = 0, x +2 y -1 = 0, 2 x +y -9 = 0, 2 x - y -7=0

4. PARAMETRIC EQUATIONS OF CIRCLE

Parametric
tric equations of the circle
(x-x1)2+(y-y1)2 =r2 are x = x1+r cosα ,
y = y1+r sinα

p = (p,q)) is the position vector of the center
so equation of tangent in parametric form is given by
S1=0 where point is (-g+r
+r cosα , -f+r sinα)
i.e, tangent to circle (x+g)2+(y+f)2 =r2 is
x( -g+r cosα)+y(-f+r sinα)+g(x-g+rcosα)+f(y-f+rsinα)+c=0 
xrcosα +rgcosα +yrsinα +rfsinα =(g2+f2-c) = r2 
(x+g) rcosα +(y+f) rsinα = r2 
(x+g) cosα +(y+f) sinα = r
As normal is perpendicular to tangent and passes through center
Slope of tangent is -tanα 
slope of normal is cotα and passes through (-g,-f)
So equation of normal is given by
(y+f) = cotα(x+g) 
(y+f) – cotα(x+g)=0

Example:
Two objects are moving on a circle with radius 2 centered at (3,4) with
angular speeds of 2 radians per second and 3 radians per second, respectively.
Parameterize the motion of each object and compare the two given that both are
at q = 0 initially.

Solution: To begin with, q= 0 initially means that t0 = 0. Thus, if we denote the
two motions by r1(t) and r2( t) , respectively, then

r1(t) =  3 + 2cos(2t), 4 + 2sin(2t) 

r2(t) =  3 + 2cos(3t), 4 + 2sin(3t) 

Moreover the second object will traverse the circle 3 times for every 2 traversals
of the circle by the first object. Indeed, r1(t) and r2(t) are shown below for ever
increasing values of t.
The fundamental period of a uniform circular motion r(t) is the smallest
positive number T for which

r( t + T) = r(T) for all T (3)

That is, T is the time it takes an object in uniform circular motion to make one
complete cycle around the circle. Since radian
ians is the angle
corresponding to one complete cycle, it follows that
T =2π/w
Thus, if we are given the period of a uniform circular motion, we can use (3) to
calculate its angular speed.
5. PROPERTIES OF CIRCLE

Power of a point Theorem:

Given a point P and a circle, pass two lines through P that intersect the circle in
points A and D and, respectively, B and C. Then AP⋅DP=BP⋅CP.
Proof:
The point P may lie either inside or outside the circle. The line through A and D
(or that through B and C or both) may be tangent to the circle, in which case A
and D coalesce into a single point. In all the cases, the theorem holds and is
known as the Power of a Point Theorem.
When the point P is inside the circle, the theorem is also known as the Theorem
of Intersecting Chords (or the Intersecting Chords Theorem) and has a
beautiful interpretation. When the point P is outside the circle, the theorem
becomes the Theorem of Intersecting Secants (or the Intersecting Secants
Theorem.)
The proof is exactly the same in all three cases mentioned above. Since triangles
ABP and CDP are similar, the following equality holds:
APCP=BPDP,
which is equivalent to the statement of the theorem: AP⋅DP=BP⋅CP.
Examples:
1) Find the value of in the following diagram.

Solution:

Applying the Power of a Point Theorem gives , or

2) In a circle, chords and intersect at . If and
, find the ratio

Solution:
Letting makes . Similarly, letting makes .
Thus and

. We therefore seek .
From the Power of a Point Theorem, we have that

,

which gives , so we take .
Finally,
Equation of chord of contact

PQ -- chord of contact
polar line of T w.r.t. the
--
circle
T -- the pole
Tangent at
--
P
x2x + y2y + g(x + x2) + f (y + y2) + C = 0
Tangent at
--
Q
x3x + y3y + g(x + x3) + f (y + y3) + C = 0

(x1, y1) lie on tangent at P and tangent at Q.
(x1, y1) satisfies both equation.
i.e. x2x1 + y2y1 + g(x1 + x2) + f (y1 + y2) + C =0
x3x1 + y3y1 + g(x1 + x3) + f (y1 + y3) + C =0
we see that (x2, y2) and (x3, y3) satisfy the equation
xx1 + yy1 + g(x1 + x) + f (y1 + y) + C =0
so equation of chord of contact to a circle S=0 is given by S1=0.

Examples:
1) If the chord of contact of the tangents drawn to x2+y2=a2 from any point on
x2+y2=b2, touches the circle x2+y2=c2, then show that a2=bc
Solution 1:
Let P(x1, y1) be any point on x2+y2=b2 i.e. x12+y12=b2. Equation of
corresponding chord of contact is S1=0 .
xx1+yy1-a2=0. It touches x2+y2=c2

Solution 2:

In OAC cos θ = OC/OA = c/a …(1)

and in OAP cos θ = a/b …(2)

from (1) and (2) a2 = bc

2) Tangents to the circle x2 + y2 = a2 cut the circle x2 + y2 = 2a2 at P and Q.
Prove that tangents at P and Q to the circle x2 + y2 = 2a2 intersect at right
angles.
Solution:
Equation of tangent at any point (a cosθ, a sin θ) to the circle x2 + y2 = a2
is xcosθ+ y sin θ = a ………(1)
Let the point of intersection of the tangents at P and Q be (h, k). If the tangents
at P and Q intersect at right angles, then locus of (h, k) will be director circle of
x2 + y2 = 2a2 i.e. x2 + y2= 4a2. PQ is chord of contact of the circle x2 + y2 =
2a2 w.r.t. the point (h, k) i.e. equation of PQ is hx + ky = 2a2 ……(2)
(1) and (2) are same equation cosθ/h = sin θ/k = a/2a2 = 1/2a
cos2θ + sin2 θ = 1 => h2 + k2 = 4a2

∴ Locus of (h,k) is x2 + y2 = 4a2 which is director circle to x2 + y2 = 2a2

6. HOMOGENIZING CIRCLE

If the line lx + my + n = 0, (n ≠ 0) i.e. the line not passing through origin) cuts
the curve ax2 + by2 + 2gx + 2fy + c = 0 at two points A and B, then the joint
equation of straight lines passing through A and B and the origin is given by
homogenizing the equation of the curve by the equation of the line. i.e.

ax2 + 2hxy + by2 + (2gx + 2fy) (kx+my/–n) + c (lx+my/–n)2 = 0.
is the equation of the lines OA and OB.
Illustration:
Prove that the straight lines joining the origin to the points of intersection of the
straight line hx + ky = 2hk and the curve (x – k)2 + (y – y)2 = c2 are at right
angles if h2 + k2 = c2.
Solution: Making the equation of the curve homogeneous with the help
of that of the line, we get
x2 + y2 –2(kx + hy) (hx+ky/2hk) + (h2 + k2 – c2) (hx+ky/2hk) = 0
or 4h2k2x2 + 4h2k2y2 – 4h2x(hx+ky) – 4h2ky(hx + ky) + (h2 + k2 – c)(h2x2 + k2y2
+ 2hxy) = 0.
This is the equation of the pair of lines joining the origin to the points of
intersection of the given line and the curve. They will be at right angles if
Coefficient of x2 + coefficient of y2 = 0 i.e.
(h2 + k2) (h2 + k2 – c2) = 0 ⇒ h2 + k2 = c2 (since h2 + k2 ≠ 0).

Thus homogenization of curve is used in all the Conics either it may be Ellipse,
Hyperbola, Parabola.